Inclusive Mathematics Education in Brazil - Penteado, Miriam Godoy [UNESP]; Marcone, Renato (Springer Nature, 2019)
The inclusive education movement in Brazil has accompanied an international movement since the last years of the twentieth century, starting with the Jomtien declaration in 1990. As far as legislation is concerned, students with disability are well represented regarding access to education from the early years to higher education, but the enforcement of this legislation still has a long way to go. However, creating the legislation is only one step towards inclusion. The very notion of what a disability means must be addressed in order to create proper and coherent laws. The research about inclusion in Brazil has grown since the first decade of the twenty-first century, going beyond research on early school years, addressing inclusion in higher education as well - in part thanks to the legislation that opened the way for those students - and showing the impact of public policies on inclusion.
Keywords: Brazil; Difference; Inclusion; Inclusion policy; Mathematics education